Effectiveness of granular columns in containing settlement - O'Kelly, Brendan (My University, 2014)
Laboratory-based research studies and full-scale evaluations of the behaviour of ground improved with granular columns are ample regarding bearing capacity, but limited in respect to the settlement response. This paper presents a laboratory model study that considers the settlement performance of isolated pad footings bearing on reinforced sand deposits under the influence of a fluctuating groundwater table. This is a particularly onerous condition for loose sand deposits in coastal areas, which may undergo significant collapse settlement over time. Loose and dense experimental sand beds were constructed, and the performance of rigid footings under a maintained load and bearing on sand incorporating different column configurations was monitored under cycling of the water table over a period of 28 d, with one filling/empting cycle every 18 h. It was found that settlement, while greatly reduced compared with that for unreinforced footings, was ongoing, and typically occurred at a much greater rate for loose sand than for dense sand. Also, settlement rates were slightly higher for fully penetrating than partially penetrating columns, and also for footings reinforced by a column group rather than a single column. This was attributed to the migration of sand grains into the larger column voids.
PUBLISHED
Keywords: Drainage and irrigation; Geotechnical engineering; Groundwater